Playing with free energy. Issue 1 (2nd July 2020) - Mathys, Christoph
ABSTRACT: Mark Solms's "New Project for a Scientific Psychology" represents an invaluable step in the direction of a generative model of the mental apparatus. In particular, the idea of drawing a connection between conscious processing and variations in the precision of predictions, is an idea worth pursuing. However, the imperative always to minimize free energy is far too limiting. There is no stronger sign of evolutionary fitness than not needing to minimize it and instead playing with it. We may therefore assume that the mental apparatus, and conscious processing especially, have evolved also in order to display their skill at allowing for and handling an abundance of free energy.